Design of quadrature amplitude modulation–based DC offset cancellation circuit. Issue 4 (1st October 2016) - Goswami, Manish; Joshi, Piyush; Pal, Dipankar
Abstract : The research work presented in this paper deals with the design of quadrature amplitude modulation (QAM)–based DC offset cancellation circuit along with the design of high-frequency quadrature ring oscillator. Such a technique uses modulation concept for cancellation of offset and offers extremely low offset. QAM is an analogue modulation scheme in which the signal is shifted to higher frequency domain and can result in elimination of DC component using filtering. The proposed work also introduces quadrature ring oscillator based on tetrahedral structure for generation of appropriate signals and design of current differencing transconductance amplifier (CDTA)–based quadrature oscillator for offset cancellation. The design when simulated on 180 nm technology using Cadence tools with ±1.5 V power supply reduces offset to −70 µV and −80 µV for two sinusoids having different phase, frequency and amplitudes. The voltage gain, power dissipation and the active silicon area using single metal, single poly process are 1000, 11.15 mW and 7071.95 µm 2, respectively. Moreover, the proposed oscillator has a frequency of 6.24 GHz, which is 50% higher than tetrahedral oscillator and can be used for many RF applications.